Relationship between knowledge and behavior levels of antibiotic usage among pharmacy patients in sub-districts puguh and tegorejo Kendal - Monica Lita Amay Sonia; Gilang Rizki Al Farizi; Ovikariani Ovikariani (Media Farmasi: Jurnal Ilmu Farmasi, 2023)
Antibiotic resistance is a very serious condition for public health care around the world. This situation is due to improper use of antibiotics that can be affected by self-medication or improper consumption of antibiotics due to lack of knowledge and lack of public awareness of antibiotic use. This study is aimed to determine the relationship of the level of knowledge of the behavior of the use of antibiotics in Pharmacy patients in sub-districts of Puguh and Tegorejo Kendal. This study was an observational study with a cross sectional approach in the research period of May-June 2022. The data collection was carried out by purposive sampling with a total of 130 respondents. The instruments used in the study are structured. Spearman test results showed that there is a relationship with the level of knowledge of antibiotic use behavior (p = <0.05) ; r = 0.549. The conclusion of the study is that there is a relationship between the level of knowledge of antibiotic use behavior in pharmacy patients in sub-districts of Puguh and Tegorejo Kendal.